Differential control of Salmonella heat shock operons by structured mRNAs. Issue 4 (11th July 2013) - Cimdins, Annika; Roßmanith, Johanna; Langklotz, Sina; Bandow, Julia E.; Narberhaus, Franz
Summary: DnaK–DnaJ–GrpE and GroES–GroEL are the major chaperone machineries in bacteria. In many species, dnaKJ and groESL are encoded in bicistronic operons. Quantitative proteomics revealed that DnaK and GroEL amounts in Salmonella dominate over DnaJ and GroES respectively. An imperfect transcriptional terminator in the intergenic region of dnaKJ is known to result in higher transcript levels of the first gene. Here, we examined the groESL operon and asked how the second gene in a heat shock operon can be preferentially expressed and found that an RNA structure in the 5′untranslated region of groES is responsible. The secondary structure masks the Shine–Dalgarno (SD) sequence and AUG start codon and thereby modulates translation of groES mRNA. Reporter gene assays combined with structure probing and toeprinting analysis revealed a dynamic temperature‐sensitive RNA structure. Following an increase in temperature, only the second of two RNA hairpins melts and partially liberates the SD sequence, thus facilitating translation. Translation of groEL is not temperature‐regulated leading to an excess of the chaperonin in the cell at low temperature. Discussion in a broader context shows how structured RNA segments can differentially control expression of temperature‐affected operons in various ways.